Being Muslim Immigrants in America: Preservation, Resistance, and Negotiation of Identity in Ayad Akhtar’s “American Dervish” - Rika Handayani (English Department, Faculty of Humanities, Andalas University, 2020)
This thesis entitled ‘Being Muslim Immigrants in America: Preservation, Resistance, and Negotiation of Identity in Ayad Akhtar’s ‘American Dervish’ aims to analyze the depiction of Muslim immigrants identity in the context of diaspora. Through the lenses of Hall’s theory of identity and Clifford’s diaspora, the analysis centered on how the Muslim immigrant characters in the novel interacted with other individuals with diverse backgrounds of race, gender, and religion. This contributed towards the construction of identity through the preservation and resistance of homeland culture, dominant culture or host land culture and the negotiation between Muslim immigrants and their state and American society. Therefore, the Muslim immigrant characters in the novel hold a non-essential and fluid identity as portrayed from the perpetual construction of identity.